Konservasi penyu di Pulau Talise, Gangga dan Bangka Kabupaten Minahasa Utara - Arunde, Preti; Boneka, Farnis B.; Wagey, Billy Th.; Mamangkey, Gustaf; Manembu, Indri; Kambey, Alex (Universitas Sam Ratulangi, 2018)
Generally, this study was intended to examine the problems or implementation of turtle conservation in Talise, Gangga and Bangka Islands and specifically with a number of objectives to: know the introduction of sea turtle, to know sea turtle fishing and turtle exploitation, to know the knowledge of the people about turtle as a protected animal. Survey results on Talise Island, Gangga and Bangka showed that people who had seen turtles directly: Talise Island 94%, Gangga 58%, and Bangka 92%. Local residents of Talise, Gangga and Bangka Islands know well the turtles even see directly in their habitat and spawning time. In Talise, Gangga and Bangka Islands, Â turtles are still commonly caught, traded and consumed by local people. Â People's awareness about turtles as protected animals is lacking. Â Keywords: Turtle, Talise Island, Gangga and Bangka